The disaster resilience value of shared rooftop solar systems in residential communities. Issue 4 (November 2021) - Patel, Siddharth; Ceferino, Luis; Liu, Chenying; Kiremidjian, Anne; Rajagopal, Ram
Distributed energy resources can enhance community resilience to power outages in the aftermath of natural disasters. This article presents a method to quantify the resilience value that rooftop solar systems can provide to residential neighborhoods. Homes are grouped into geographical clusters to simulate the effect of sharing energy when a disaster disables the electric grid and damages some of the homes. Historical energy consumption and solar irradiance data are used to estimate the likelihood that each cluster could meet its own energy needs, given a defined level and pattern of rooftop solar adoption. As a case study, the method is applied to single-family homes in San Carlos, California, subjected to a disaster scenario representing the 1906 San Francisco earthquake. The case study shows how higher rooftop solar adoption levels increase postearthquake power accessibility during different seasons of the year. It also demonstrates that policy intervention can ensure more geographically uniform solar adoption and, therefore, more even resilience. Finally, the article evaluates the effect and cost of such an intervention, finding that a modest subsidy can make a notable difference in evening out resilience across a community.